Unilateral nevoid telangiectasia: A rare disease? - Rita Guedes; L Leite (Wolters Kluwer Medknow Publications, 2012)
Unilateral nevoid telangiectasia is a rare congenital or acquired disorder. The majority of the authors propose that it is probably related to elevated estrogen receptors, although other authors advocate different theories. We report the occurrence of lesions clinically compatible with this diagnosis in a child and two adults. Only one of the patients had a background of estrogen elevation. The other two patients were healthy. We stress the occurrence of this disease in a rare idiopathic form and point out to the relative elevated incidence of it, because the patients discussed in this article were observed for a short period of time.